Oral nutritional supplementation with dietary counseling improves linear catch-up growth and health outcomes in children with or at risk of undernutrition: a randomized controlled trial - Ow, Mandy Y. L.; Tran, Nga Thuy; Berde, Yatin; Nguyen, Tu Song; Tran, Van Khanh; Jablonka, Morgan J.; Baggs, Geraldine E.; Huynh, Dieu T. T. (Frontiers in Nutrition, 2024)
Childhood undernutrition is associated with increased morbidity, mortality and a high socioeconomic burden. Supporting Pediatric GRowth and Health OUTcomes (SPROUT) is a randomized, controlled trial evaluating the effects of an oral nutritional supplement (ONS) with dietary counseling (DC) (n = 164) compared to a DC-only group who continued consuming their habitual milk (n = 166) (NCT05239208). Children aged 24-60 months who were at risk or with undernutrition, as defined by weight-for-age [WAZ] < -1 and height-for-age [HAZ] < -1 according to the WHO Growth Standards, and who also met the criterion of weight-for-height [WHZ] < 0, were enrolled in Vietnam. ONS+DC had a larger WAZ increase at day 120 (primary endpoint) vs. DC (least squares mean, LSM (SE): 0.30 (0.02) vs. 0.13 (0.02); p <0.001), and larger improvements in all weight, BMI and weight-for-height indices at day 30 and 120 (all p <0.01). Height gain was larger in ONS+DC in all indices, including height-for-age difference (HAD) (cm: 0.56 (0.07) vs. 0.10 (0.07); p <0.001), at day 120. ONS+DC had larger arm muscle but not arm fat indices, higher parent-rated appetite, physical activity and energy levels, longer night sleep, fewer and shorter awakenings, and better sleep quality than DC. Adding ONS to DC, compared to DC-alone, improves growth in weight and height, linear catch-up growth, and health outcomes in children with or at risk of undernutrition.